Authorship Distribution and Under-Representation of Sub-Saharan African Authors in Global Oncology Publications - Hubert Tuyishime; Paula Hornstein; Nwamaka Lasebikan; Fidel Rubagumya; Miriam Mutebi; Temidayo Fadelu (JCO Global Oncology, 2022)
PURPOSELocal researchers must be engaged in research conducted in their populations. However, local authors from low- and middle-income countries are often under-represented in global health journals. This report aims to assess and describe the representation of authors in the Journal of Clinical Oncology Global Oncology (JCO GO).METHODSThis retrospective cross-sectional study describes data from JCO GO articles published between October 2015 and March 2020. Data were collected on studied countries, authorship position, classified as first, middle, or last, and country of authors' institutional affiliations. Countries were then categorized on the basis of their World Bank region and income classifications. We describe aggregate authorship distribution and distribution by region and income classification. Additionally, we explore the relationships between author's country and studied country.RESULTSOf the 608 articles identified, 420 (69.1%) studied a single country population. Although articles represented studies from all World Bank regions, the sub-Saharan Africa (SSA) region accounted for the highest number (n = 145; 34.5%). In all other regions except SSA, most of the first (66.7%-100%) and last authors (56.6%-95.2%) had primary institutional affiliations based in the same region as the studied country. However, among articles about SSA countries, SSA first authors (n = 65; 44.8%) and last authors (n = 59; 40.7%) were under-represented. In fact, there were more North American first (n = 74; 51.0%) and last authors (n = 72; 49.6%) than SSA authors. There was higher SSA representation among middle authors (n = 97; 68.8%) in studies from the region. A similar trend was also noted with the under-representation of authors from low-income compared with high-income countries.CONCLUSIONSSA authors are under-represented in global oncology articles. Concerted strategies are needed to build local capacity, promote meaningful engagement, and foster equity.